Polymeric nanoparticles enhance the sonodynamic activity of meso-tetrakis (4-sulfonatophenyl) porphyrin in an in vitro neuroblastoma model - Canaparo R (Dove Medical Press, 2013)
Roberto Canaparo,1,* Greta Varchi,2,* Marco Ballestri,2 Federica Foglietta,1 Giovanna Sotgiu,2 Andrea Guerrini,2 Andrea Francovich,3 Pierluigi Civera,3 Roberto Frairia,4 Loredana Serpe1 1Department of Drug Science and Technology, University of Torino, Torino, Italy; 2Institute of the Organic Synthesis and Photoreactivity, National Research Council, Bologna, Italy; 3Departments of Electronics, Politecnico of Torino, Torino, Italy; 4Department of Medical Science, University of Torino, Torino, Italy *These authors contributed equally to this work Purpose: Sonodynamic therapy is a developing noninvasive modality for cancer treatment, based on the selective activation of a sonosensitizer agent by acoustic cavitation. The activated sonosensitizer agent might generate reactive oxygen species leading to cancer cell death. We investigated the potential poly-methyl methacrylate core-shell nanoparticles (NPs) loaded with meso-tetrakis (4-sulfonatophenyl) porphyrin (TPPS) have to function as an innovative sonosensitizing system, ie, TPPS-NPs. Methods: Shockwaves (SWs) generated by a piezoelectric device were used to induce acoustic cavitation. The cytotoxic effect of the sonodynamic treatment with TPPS-NPs and SWs was investigated on the human neuroblastoma cell line, SH-SY5Y. Cells were exposed for 12 hours to TPPS-NPs (100 µg/mL) and then to SWs (0.43 mJ/mm2 for 500 impulses, 4 impulses/second). Treatment with SWs, TPPS and NPs alone or in combination was carried out as control. Results: There was a statistically significant decrease in SH-SY5Y cell proliferation after the sonodynamic treatment with TPPS-NPs and SWs. Indeed, there was a significant increase in necrotic (16.91% ± 3.89%) and apoptotic (27.45% ± 3.03%) cells at 48 hours. Moreover, a 15-fold increase in reactive oxygen species production for cells exposed to TPPS-NPs and SWs was observed at 1 hour compared with untreated cells. A statistically significant enhanced mRNA (messenger ribonucleic acid) expression of NRF2 (P<0.001) and a significant downregulation of TIGAR (P<0.05) and MAP3K5 (P<0.05) genes was observed in cells exposed to TPPS-NPs and SWs at 24 hours, along with a statistically significant release of cytochrome c (P<0.01) at 48 hours. Lastly, the sonosensitizing system was also investigated in an in vitro three-dimensional model, and the sonodynamic treatment significantly decreased the neuroblastoma spheroid growth. Conclusion: The sonosensitizing properties of TPPS were significantly enhanced once loaded onto NPs, thus enhancing the sonodynamic treatment's efficacy in an in vitro neuroblastoma model. Keywords: poly-methyl methacrylate nanoparticles, sonodynamic therapy, ultrasound, shockwaves, cancer